2017
DOI: 10.12693/aphyspola.131.1373
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure of Small Amount of TM Added Al-Mg-Si Alloys with Two-Step Ageing

Abstract: Traditionally, Al-Mg-Si alloys are strengthened by dispersed small particles and they have medium strength with good formability. It is well known that alloying elements on Al-Mg-Si alloys (e.g. Cu) can improve mechanical properties because Cu can alter precipitation sequence. In this research, we investigated the effect of transition metals (TM) on Al-1.06at.%MgSi-TM alloys through single-and two-step ageing. Mechanical property and microstructure observation were conducted by micro Vickers hardness measureme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Kuroda et al studied the effect of small amounts of Ni, Co, and V on hardness after age hardening of the AlMgSi base alloy. It was found that the additives increase the hardness, with the highest value of hardness occurring after the introduction of Ni and two-stage aging [16].…”
Section: XXX Series Aluminum Alloys For Extrusion Of Shapesmentioning
confidence: 99%
“…Kuroda et al studied the effect of small amounts of Ni, Co, and V on hardness after age hardening of the AlMgSi base alloy. It was found that the additives increase the hardness, with the highest value of hardness occurring after the introduction of Ni and two-stage aging [16].…”
Section: XXX Series Aluminum Alloys For Extrusion Of Shapesmentioning
confidence: 99%